English Teachers Classroom Management : Cultivating Students Creativity in Indonesian Junior High School - Vevi Khoiriawati; Melvina Melvina; Rika Afriyanty (English Teaching and Linguistics Journal (ETLiJ), 2023)
This study aims to find out how the creativity of a teacher in managing the class to foster student creativity at SMP Negeri 12 Tebo Regency. The object of this research is an English subject teacher at SMP Negeri 12 Tebo Regency. The method used is descriptive qualitative method in the form of survey research. Data was taken by direct communication techniques, namely in the form of interviews. While the data processing technique is using deduction reasoning, which means drawing conclusions from the general to the specific. Deductive reasoning is drawing conclusions from a general premise or assumption to make a special logical conclusion. The results showed that the English teacher at SMP N 12 Tebo Regency already had criteria for a creative teacher in the teaching and learning process, such as the teacher already had a great curiosity when teaching, the teacher already had a flexible nature, the teacher already had a sense of humor, the teacher already have an inspiring nature, the teacher already has a positive and empathetic attitude, the teacher has dared to take risks, such as instructing students to make media that will be used for learning and the teacher has also used existing facilities or media.